PhET Simulations in Undergraduate Physics - Mary Gene Saudelli; Robin Kleiv; Jessica Davies; Martin Jungmark; Rebecca Mueller (Brock University, 2021)
Computer simulation educational technologies provide a convenient way of augmenting learning. Simulation technologies have been used and researched in higher education classrooms in fields such as medicine (e.g: Al-Elq, 2010), nursing (Kim, Park & Shin, 2016), and chemistry (Cheng, 2017), among others.  The University of Colorado Boulder has created a large number of Physics Education Technology (PhET) computer simulations relevant to concepts in Physics, Chemistry, Biology, Earth Science and Mathematics. These PhETs have been studied in relation to teaching in elementary and secondary schooling (i.e. Hensberry, Moore, Perkins, 2015). However, there is a notable gap in the literature that speaks to the connection of simulation based technologies, learning theories, and pedagogy in practice relation to teaching Physics in higher education.  This action research study seeks address that gap by exploring the role of the specific and intentional inclusion of Physics Education Technology (PhET) in the curriculum and teaching practice of an undergraduate Physics class in a Canadian university.  Findings centre on the theme of teaching practice change, and discovery that PhETs have value as a more capable peer in relation to Vygotsky's (1978) zone of proximal development.